Micro-Electro-Mechanical Systems (MEMS) 1998
DOI: 10.1115/imece1998-1290
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Tape-Based Meso Systems Technology

Abstract: Ceramic tape technology was initially developed for efficiently manufacturing interconnects and hybrid microelectronics circuitry through sequential printing and firing of conductor, resistor and/or dielectric paste formulations onto a substrate. Recently, it has been recognized that ceramic tapes can also be used as an efficient and convenient medium for the manufacturing of meso-scale electro-mechanical systems. In the green (pre-fired) state, the ceramic tapes consist of alumina particles, glass frit, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The work carried out over the past five years at the University of Pennsylvania has demonstrated that ceramic tapes can also be used as an efficient and convenient medium for the manufacture of meso-scale (millimeter to centimeter size) integrated fluidic systems (Bau et al 1998, Espinoza-Vallejos andSantiago-Aviles 2000). In the green state, the LTCC tapes are very flexible and soft which makes it easy to machine them.…”
Section: Ltcc Tapes For Integrated Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work carried out over the past five years at the University of Pennsylvania has demonstrated that ceramic tapes can also be used as an efficient and convenient medium for the manufacture of meso-scale (millimeter to centimeter size) integrated fluidic systems (Bau et al 1998, Espinoza-Vallejos andSantiago-Aviles 2000). In the green state, the LTCC tapes are very flexible and soft which makes it easy to machine them.…”
Section: Ltcc Tapes For Integrated Microfluidicsmentioning
confidence: 99%
“…In order to make conduits of various shapes, milling is more versatile and avoids the step-pattern of punching. Using 125 µm and 250 µm diameter mill bits, holes and slots of arbitrary shape are milled in a single layer of LTCC tape using a computer numerically controlled (CNC) machine (Bau et al 1998, Kim et al 1999.…”
Section: Ltcc Tapes For Integrated Microfluidicsmentioning
confidence: 99%
“…In addition to the possibility of creating complex three-dimensional structures, LTCC devices, once fired, are thermally stable compared to silicon devices, which generally work best at or near room temperature, 22 °C. Moreover, LTCC devices have been shown to work at temperatures exceeding 150 °C . Another important advantage of the LTCC systems is that the devices are self-packaged; thus, there is no need to mount the completed device onto a substrate.…”
mentioning
confidence: 99%